2016
DOI: 10.1002/brb3.422
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying brain volumes for Multiple Sclerosis patients follow‐up in clinical practice – comparison of 1.5 and 3 Tesla magnetic resonance imaging

Abstract: IntroductionThere is emerging evidence that brain atrophy is a part of the pathophysiology of Multiple Sclerosis (MS) and correlates with several clinical outcomes of the disease, both physical and cognitive. Consequently, brain atrophy is becoming an important parameter in patients' follow‐up. Since in clinical practice both 1.5Tesla (T) and 3T magnetic resonance imaging (MRI) systems are used for MS patients follow‐up, questions arise regarding compatibility and a possible need for standardization.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…In line with other recent studies, 23,25,26 the MS-MRIUS study showed that scanner changes had an impact on brain volume estimates. While it was previously shown that NeuroSTREAMderived PLVVC is relatively robust to different field strengths when imaged during a short time (approximately 2% coefficient of variation in the 1.5T versus 3T scan-rescan test for 72 hours), 23 the current study showed that PLVVC on T2-FLAIR was significantly different in patients with RRMS with hardware changes, compared with those without.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with other recent studies, 23,25,26 the MS-MRIUS study showed that scanner changes had an impact on brain volume estimates. While it was previously shown that NeuroSTREAMderived PLVVC is relatively robust to different field strengths when imaged during a short time (approximately 2% coefficient of variation in the 1.5T versus 3T scan-rescan test for 72 hours), 23 the current study showed that PLVVC on T2-FLAIR was significantly different in patients with RRMS with hardware changes, compared with those without.…”
Section: Discussionsupporting
confidence: 90%
“…24 All outcomes of brain atrophy analyses were assessed by an experienced rater. Because hardware changes can affect longitudinal measurements, [25][26][27] SIENA PBVC and VIENA PLVVC analyses were considered invalid when a patient was imaged on different hardware. In addition, because Neuro-STREAM PLVVC was previously shown to be robust to hardware changes in a study that included 125 patients with MS and 76 healthy controls, 23 we explored the stability of this measure in patients with and without MR imaging hardware changes using the current real-world setting dataset.…”
Section: Methodsmentioning
confidence: 99%
“…MSmetrix has a separate cross-sectional and longitudinal pipeline of which the details are published elsewhere ( Jain et al, 2015 , Lysandropoulos et al, 2016 , Smeets et al, 2016 ). In short, the cross-sectional pipeline combines lesion segmentation, lesion filling and tissue segmentation in an iterative algorithm that converges to segmentations that allow for measurement of lesion volume, whole-brain volume (BV), and gray matter volume (GMV).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the MSmetrix software package (Icometrix, Flanders, Belgium) has received CE labeling and FDA approval for the automatic quantification of cerebral (and WM lesion) volumes from FLAIR and T1-weighted images in patients with MS ( Jain et al, 2015 , Lysandropoulos et al, 2016 , Smeets et al, 2016 ). MSmetrix accepts any of these clinical sequences (FLAIR with a maximum slice thickness of 3 mm) and generates an online report with the measured white matter lesion, whole-brain and gray matter volumes.…”
Section: Introductionmentioning
confidence: 99%
“…The MSmetrix does not require manual interface and/or training and seems to be more accurate than SIENA when different field strengths are used 44 . When MSMetrics, SIENA and NeuroQuant are compared, the level of discrepancy among them varies from 1% to 5.5% 41 .…”
mentioning
confidence: 99%